2016
DOI: 10.3390/ijms17101772
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response to XD14 Treatment in Human Breast Cancer Cell Line MCF-7

Abstract: XD14 is a 4-acyl pyrrole derivative, which was discovered by a high-throughput virtual screening experiment. XD14 inhibits bromodomain and extra-terminal domain (BET) proteins (BRD2, BRD3, BRD4 and BRDT) and consequently suppresses cell proliferation. In this study, metabolic profiling reveals the molecular effects in the human breast cancer cell line MCF-7 (Michigan Cancer Foundation-7) treated by XD14. A three-day time series experiment with two concentrations of XD14 was performed. Gas chromatography-mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Analysis of cell culture media: Metabolites from cell culture medium were extracted as previously reported by acetonitril:methanol 44 . Pellets were analyzed by GC/MS profiling in the same manner as endometabolites 48 . Instead of peak sum normalization, only the internal standard as well as a correction (17:12) for dilution introduced by the NaCl rinsing in 3D cultures was applied for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of cell culture media: Metabolites from cell culture medium were extracted as previously reported by acetonitril:methanol 44 . Pellets were analyzed by GC/MS profiling in the same manner as endometabolites 48 . Instead of peak sum normalization, only the internal standard as well as a correction (17:12) for dilution introduced by the NaCl rinsing in 3D cultures was applied for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the protocol of Fiehn ( 2006 ), sample derivatization, gas chromatography–mass spectrometry (GC–MS) analysis and data evaluation were performed as described by Pan et al ( 2016 ). Briefly, the prewarmed pellets were derivatized by shaking with 20 µL 20 mg/mL methoxyamine hydrochloride (Sigma-Aldrich, Germany) in pyridine (Sigma-Aldrich, Germany) at 1200 rpm and 28 °C for 90 min and, after short centrifugation, with 50 µL N -methyl- N -trimethylsilyltrifluoroacetamide (Sigma-Aldrich, Germany) at 1200 rpm and 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations of metabolites have been reported in blood plasma, urine of cancer patients and cancer cell lines, providing promising possibilities of biomarker discoveries (Bullinger et al 2007 ; Frickenschmidt et al 2008 ; Asiago et al 2010 ; Shen et al 2013 ; Armitage and Barbas 2014 ; Willmann et al 2015 ). Additionally, metabolomics helps in understanding cellular mechanisms by showing the metabolic status of drug-treated or non-treated cancer cells (Jain et al 2012 ; Budczies et al 2015 ; Pan et al 2016 ). Since metabolomics has been described as the link between genotype and phenotype (Fiehn 2002 ), Stefely et al ( 2016 ) have profiled 174 yeast strains with different single gene knockouts to elucidate the mitochondrial protein functions.…”
Section: Introductionmentioning
confidence: 99%
“…Functional endpoints relevant to a response biomarker would include cell death or a reduction in cell proliferation. Unfortunately, most in-vitro studies on drug-induced changes in the metabolome primarily involve a description of changes in the metabolome that result from the drug itself, or it is unclear whether the changes are pharmacologic or due to impairment of tumor cell expansion [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Serial Monitoring Of the Metabolomementioning
confidence: 99%
“…In-vitro experiments occur in defined spaces, where it is possible to see changes in metabolite concentrations in the extracellular space due to fluxes with the intracellular compartment, alterations in cellular metabolism, or due to a massive release from cell lysis. In vivo, the metabolome could be affected by a variety of tumor and host factors, which is why we and others have observed that not all cancer-associated features in the circulating metabolome can be attributed to the metabolic perturbations characteristic of a cancer cell [ 52 , 57 , 58 ]. Indeed, it is well known that in-vivo observations do not recapitulate what is observed in cell line experiments [ 59 ].…”
Section: Serial Monitoring Of the Metabolomementioning
confidence: 99%